An 8-Fold Parallel Reactor System for Combinatorial Catalysis Research. (2006) - Stoll, Norbert; Allwardt, Arne; Dingerdissen, Uwe; Thurow, Kerstin
Abstract : Increasing economic globalization and mounting time and cost pressure on the development of new raw materials for the chemical industry as well as materials and environmental engineering constantly raise the demands on technologies to be used. Parallelization, miniaturization, and automation are the main concepts involved in increasing the rate of chemical and biological experimentation.